Development and Validation of a GC-FID Method for the Quantitation of Δ8-Tetrahydrocannabinol and Impurities Found in Synthetic Δ8-Tetrahydrocannabinol and Vaping Products - Gul, Waseem; Shahzadi, Iram; Sarma, Nandakumara; Kim, Nam-Cheol; ElSohly, Mahmoud A. (Planta Medica, 2024)
Concerns about health hazards associated with the consumption of trans-delta-8-tetrahydrocannabinol products were highlighted in public health advisories from the U. S. Food and Drug Administration and U. S. Centers for Disease Control and Prevention. Simple and rapid quantitative methods to determine trans-delta-8-tetrahydrocannabinol impurities are vital to analyze such products. In this study, a gas chromatography-flame ionization detection method was developed and validated for the determination of delta-8-tetrahydrocannabinol and some of its impurities (recently published) found in synthesized trans-delta-8-tetrahydrocannabinol raw material and included olivetol, cannabicitran, Δ8-cis-iso-tetrahydrocannabinol, Δ4-iso-tetrahydrocannabinol, iso-tetrahydrocannabifuran, cannabidiol, Δ4,8-iso-tetrahydrocannabinol, Δ8-iso-tetrahydrocannabinol, 4,8-epoxy-iso-tetrahydrocannabinol, trans-Δ9-tetrahydrocannabinol, 8-hydroxy-iso-THC, 9α-hydroxyhexahydrocannabinol, and 9β-hydroxyhexahydrocannabinol. Validation of the method was assessed according to the International Council for Harmonization guidelines and confirmed linearity with R2 ≥ 0.99 for all the target analytes. The limit of detection and limit of quantitation were 1.5 and 5 µg/mL, respectively, except for olivetol, which had a limit of detection of 3 µg/mL and a limit of quantitation of 10 µg/mL. Method precision was calculated as % relative standard deviation and the values were less than 8.4 and 9.9% for the intraday precision and inter-day precision, respectively. The accuracy ranged from 85 to 118%. The method was then applied to the analysis of 21 commercially marketed vaping products claiming to contain delta-8-tetrahydrocannabinol. The products analyzed by this method have various levels of these impurities, with all products far exceeding the 0.3% of trans-Δ9-tetrahydrocannabinol limit for hemp under the Agriculture Improvement Act of 2018. The developed gas chromatography-flame ionization detection method can be an important tool for monitoring delta-8-tetrahydrocannabinol impurities in commercial products.
Keywords: Cannabis sativa; Cannabaceae; cannabinoids; GC/FID; Δ8-THC; impurities